Physiochemical and Phytochemical Properties of Wax Apple (Syzygium samarangense Blume Merrill & L. M. Perry var. Jambu Madu) as Affected by Growth Regulator Application - Khandaker, Mohammad Moneruzzaman; Boyce, Amru Nasrulhaq; Hossain, A.B.M.S.; Osman, Normaniza (2012)
This study represents the first paper of the effects of growth regulators on the physiochemical and phytochemical properties of the wax apple fruit, a widely cultivated fruit tree in southeast Asia. Net photosynthesis, sucrose phosphate synthase (SPS) activity, peel color, fruit firmness, juice content, pH value, total soluble solids (TSSs), and the sugar acid ratio were all significantly increased in growth regulators (PGRs) treated fruits. The application of gibberellin (GA(3)), naphthalene acetic acid (NAA), and 2,4-dichlorophenoxy acetic acid (2,4-D) significantly reduced titratable acidity and increased total sugar and carbohydrate content compared to the control. The 50 mg/L GA(3), 10 mg/L NAA, and 5 mg/L 2,4-D treatments produced the greatest increases in phenol and flavonoid content; vitamin C content was also higher for these treatments. PGR treatment significantly affected chlorophyll, anthocyanin, and carotene content and produced higher phenylalanine ammonia lyase (PAL) and antioxidant activity levels. There was a positive correlation between peel color and TSS and antioxidant activity and both phenol and flavonoid content and PAL activity and anthocyanin formation. A taste panel assessment was also performed, and the highest scores were given to fruits that had been treated with GA(3) or auxin. The study showed that application of 50 mg/L GA(3), 10 mg/L NAA, and 5 mg/L 2,4-D once a week from bud development to fruit maturation increased the physiochemical and phytochemical properties of wax apple fruits.